2022
DOI: 10.7554/elife.74107
|View full text |Cite
|
Sign up to set email alerts
|

Common coupling map advances GPCR-G protein selectivity

Abstract: Two-thirds of human hormones and one-third of clinical drugs act on membrane receptors that couple to G proteins to achieve appropriate functional responses. While G protein transducers from literature are annotated in the Guide to Pharmacology database, two recent large-scale datasets now expand the receptor-G protein 'couplome'. However, these three datasets differ in scope and reported G protein couplings giving different coverage and conclusions on GPCR-G protein signaling. Here, we report a common couplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 37 publications
4
99
0
2
Order By: Relevance
“…Indeed, 27% of the receptors coupling to G i/o only activated this subtype family in comparison to 0, 2.4 and 9.1% for receptors activating G 12/13 , G q/11 , and G s , respectively, thus displaying more promiscuous coupling. A detailed comparative analysis of the selectivity profiles that we observed using the EMTA sensors with that of the chimeric G protein-based assay developed by Inoue et al, 2019 and the IUPHAR/BPS Guide to Pharmacology database (GtP; https://www.guidetopharmacology.org/ ) is presented in the accompanying paper ( Hauser et al, 2022 ). Supplementary file 2C allows a direct comparison of the relative potency determined using EMTA for both the new and the already known (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, 27% of the receptors coupling to G i/o only activated this subtype family in comparison to 0, 2.4 and 9.1% for receptors activating G 12/13 , G q/11 , and G s , respectively, thus displaying more promiscuous coupling. A detailed comparative analysis of the selectivity profiles that we observed using the EMTA sensors with that of the chimeric G protein-based assay developed by Inoue et al, 2019 and the IUPHAR/BPS Guide to Pharmacology database (GtP; https://www.guidetopharmacology.org/ ) is presented in the accompanying paper ( Hauser et al, 2022 ). Supplementary file 2C allows a direct comparison of the relative potency determined using EMTA for both the new and the already known (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, this comparison only considers the final reported couplings that in the Inoue’s study were based on the criteria of positive coupling if LogRAi ≥ –1 and negative coupling if LogRAi ≤ –1, and is influenced by the different cut-offs and normalization used in the two studies. A comparison of couplings using common E max standard deviation cut-off, quantitative normalization and aggregation of G proteins into families is provided in the accompanying paper ( Hauser et al, 2022 ). As can be seen in Supplementary file 4A , among the 70 receptors common to both studies, less couplings were detected in our study than reported in Inoue et al for Gα s (21 vs. 28), Gα i1 (54 vs. 56), Gα q (31 vs. 34), and Gα 14 (36 vs. 40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on the 41 genetic variants found in GIP(1-42) to dissect different peptide regions as they exhibit differential features with respect to receptor interaction. Taking the twodomain binding mechanism into account (35), GIP(1-42) was divided into three segments: a N-terminal segment (residue 1-15), a core segment (residue 16-30), and a C-terminal segment (residue [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Mapping Conserved Positions and Detrimental Variants Within ...mentioning
confidence: 99%